(untitled) (Research, Society and Development, 2024)
The nasal bones are the most commonly fractured bones in the face due to their anatomical location and thin thickness, even with low-intensity traumas. Because of their high incidence, clinical and imaging diagnosis is important for proper case management, considering their complexity. Given their frequency, clinical criteria are established and must be carefully evaluated, along with different treatment approaches based on the complexity of each case. The article in question reports on closed reduction of a nasal fracture under general anesthesia. The patient, a victim of physical assault, presented with clinical signs including epistaxis, crepitus, nasal obstruction, and rhinoescoliosis. This article aims to describe the clinical case of nasal fracture from diagnosis to clinical management, comparing observed and performed actions with current literature. It was concluded that closed reduction technique for nasal fractures proves to be an effective and safe approach, with benefits including not only restoration of nasal aesthetic and functional aspects but also minimization of postoperative complications. The patient is currently under follow-up with the team, showing no signs of aesthetic or functional compromise.